Trying to grow like a weed : the impact of partial harvests on Alaria esculenta yield, quality, and cost - Koester, Jennifer Aimee, 1997- (2022)
While seaweed aquaculture is generally promising from industry and ecological perspectives, most companies fail to become entirely profitable. This study aims to compare the impact of using two partial harvests to a single harvest on seaweed yield, biofouling, chemical composition, cost, and consumer preferences for Alaria esculenta farmed in the Faroe Islands. The study also aims to help identify ideal, cost-efficient harvesting methodologies that ensure the financial and ecological success of the industry. During the study, 50-meter-long lines were either trimmed in harvest 1 (June 2021) and entirely harvested in harvest 2 (August 2021, partial harvest), entirely harvested in harvest 1 (total harvest), or left unharvested during harvest 1 and 2 (control). Yield, biofouling, chemical composition, and economic analyses were compared between each trial. Partial harvests did not significantly impact the harvest wet weight compared to a total harvest, and blade length decreased from harvest 1 (70-80 cm) to harvest 2 (46-57 cm). Biofouling cover in harvest 1 (1-4% cover) was signficantly lower than harvest 2 (7-8% cover) and showed a succession of epibionts from filamentous algae in harvest 1 to bryozoan in harvest 2. Biofouling likely reduced the growth of harvest 2 lines. Harvest 2 biomass was too fouled to be sold as human food, and harvest 1 had 3.5 times higher concentrations of bioactivity measurements (TPC) compared to harvest 2. However, all concentrations of potentially harmful elements peaked in harvest 1, potentially representing the bioabsorptive properties of A. esculenta without epibionts. Economically, average cost per kg (dry weight) seaweed was 1.4-1.7 times lower in the total harvest compared to the partial harvest. These results indicate that partially harvesting seaweed is not an effective method to increase yield and quality or reduce costs. Developing good farming methods is essential for the environmental sustainability of seaweed farming. This study also indicates that harvest timing is more ...